Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan di BSI KCP Kuala Meulaboh - Murtaza. ZD; Nur Hafifah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The policies decided regarding employee interests have not considered employee aspirations and the lack of adequate coordination of targets and action plans at each level of the organization indicates poor communication between leaders or management and employees at BSI KCP Kuala Meulaboh. Leadership and work environment are benchmarks for determining employee performance in relation to measuring how far the employee's contribution or results are for the company. The purpose of this study was to determine the effect of leadership and work environment on employee performance at BSI KCP Kuala Meulaboh. The location of this study was at the KCP Kuala Meulaboh Office located on Jalan Meulaboh - Jeuram Gampong Simpang Peut, Nagan Raya Regency. The sample in this study was 17 employees of BSI KCP Kuala Meulaboh. The objects of this study were leadership, work environment and employee performance. Based on the results of the study, it shows that partially leadership influences employee performance with a significant value of 0.004 (<0.05) and partially the work environment influences employee performance with a significant value of 0.001 (<0.05). Simultaneously (F test), human relations and physical work environment have a significant effect on the work ethic of BSI KCP Nagan Raya 1 employees, with a significance value of (0.000 <0.05). Therefore, the results of this study state that both independent variables support the hypothesis. While the magnitude of the influence of the two variables (leadership and work environment) on employee performance is 57.2% and the remaining 42.8% is influenced by other variables not included in the research model.